Objective sleep characteristics and continuous glucose monitoring profiles of type 2 diabetes patients in real‐life settings. Issue 3 (20th December 2022) - Zhao, Yan; Zheng, Yuchan; Tian, Yixin; Yu, Qian; Qin, Lijun; Xu, Kai; Sun, Biao; Benedict, Christian; Chen, Baoyi; Wei, Lijun; Tan, Xiao
Abstract: Aim: To investigate the association between objective sleep parameters and glycaemic variability determined by continous glucose monitoring (CGM) among patients with type 2 diabetes, given the significant role of sleep in glycaemic control. Methods: In this study, CGM was carried out in 28 patients with T2D (aged 62.3 ± 4.8 years, 57% women). Sleep characteristics were assessed by actigraphy within the CGM period. CGM‐derived outcomes included glucose level, and percentages of time in range (TIR) and time above range (TAR) during the monitoring period. Associations between intraindividual night‐to‐night variations in sleep characteristics and overall CGM outcomes were analysed using linear regression. Associations between sleep characteristics during each night and time‐matched CGM outcomes were analysed using linear mixed models. Results: A total of 249 person‐days of CGM, coupled with 221 nights of sleep characteristics, were documented. Greater standard deviation (SD) of objective sleep duration (minutes) between measurement nights was associated with higher glucose level (coefficient 0.018 mmol/L [95% confidence interval CI 0.004, 0.033], P = 0.017), smaller proportion of TIR (% in observation period; coefficient −0.20% [95% CI −0.36, −0.03], P = 0.023), and greater proportion of TAR (coefficient 0.22% [95% CI 0.06, 0.39], P = 0.011). Later sleep midpoint (minutes from midnight) was associated with greater SD of glucose during the same sleep period (coefficient 0.002 minutes [95% CI 0.0001, 0.003], P = 0.037), longer nocturnal sleep duration was associated with smaller coefficient of variation of glucose level in the upcoming day (−0.015% [95% CI −0.03, −0.001], P = 0.041). Conclusion: Objectively determined sleep duration and sleep midpoint, as well as their daily variability, are associated with CGM‐derived glucose profiles in T2D patients.